Potensi Dan Penyerapan Tenaga Kerja Industri Pengolahan Di Provinsi Kepulauan Riau Tahun 2015-2019 - Mulyadi (Program Studi Ekonomi Pembangunan, 2022)
The purpose of this study is to analyze the manufacturing sector which has the potential to increase employment and the effect of the number of industries, the GRDP of the manufacturing industry and the minimum wage on employment in the Riau Islands Province in 2015-2019. The method used in this research uses 2 methods, namely Klassen typology and panel data regression. The results of the research from the classification typology show that industries with potential employment or still developing rapidly (Quadrant III) consist of 4 industries. And the results of the panel data regression research show that the number of industries and the minimum wage have a positive and significant effect on employment. Meanwhile, the GRDP of the processing industry has a negative and significant effect on employment